2000
DOI: 10.1002/1522-2683(20000601)21:11<2243::aid-elps2243>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Poisson peak harvesting for high throughput protein identification

Abstract: High throughput identification of proteins by peptide mass fingerprinting requires an efficient means of picking peaks from mass spectra. Here, we report the development of a peak harvester to automatically pick monoisotopic peaks from spectra generated on matrix-assisted laser desorption/ionisation time of flight (MALDI-TOF) mass spectrometers. The peak harvester uses advanced mathematical morphology and watershed algorithms to first process spectra to stick representations. Subsequently, Poisson modelling is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
84
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 20 publications
0
84
0
Order By: Relevance
“…The isotopic distributions of sulphurcontaining peptides are different from those of nosulphur peptides. This indicates that, in contrast to the assumption made by Breen et al [3], the effect of sulphur should not be ignored in the approximation of the distributions.…”
Section: Methodsmentioning
confidence: 78%
See 3 more Smart Citations
“…The isotopic distributions of sulphurcontaining peptides are different from those of nosulphur peptides. This indicates that, in contrast to the assumption made by Breen et al [3], the effect of sulphur should not be ignored in the approximation of the distributions.…”
Section: Methodsmentioning
confidence: 78%
“…Breen et al [3] suggested to approximate the result of the multinomial expansion (i.e., the expected proportional heights of different isotopic peaks) by a Poisson distribution. To compute the distribution, its mean, say M, needs to be known.…”
Section: Poisson Approximationmentioning
confidence: 99%
See 2 more Smart Citations
“…Automated mono-isotopic peak detection algorithms, e.g. [11][12][13][14], work excellently on strong spectra but their performance is often insufficient on weak spectra. This is unsatisfying since strong spectra are often produced by high abundant proteins, which typically represent the bulk of the cell activity.…”
Section: Introductionmentioning
confidence: 99%